Enhancing customer service experience through customer involvement and familiarity in Malaysian public universities / Mazlina Mamat ...[et al.] - Mamat, Mazlina; Mat Nawi, Farahiyah Akmal; Nik Abdul Latif, Nik Kamaruzaman; Abu Bakar, Hatinah (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2016)
Growing competition among Malaysian public universities makes it imperative to understand the important role of customer service experience in today’s higher education service environment. As a pillar of the university, Academic Affairs Department (AAD) isentrusted to meet the needs and demands of its customers especially the academic staff of the university. In service organizations, like public universities, employee (academic staff) service experience directly correlates with student satisfaction and university performance. Therefore, it is crucial to understand the factors that influence academic staff’s service experience. Hence, the primary focus of this study is to examine the relationship of involvement and familiarity in influencing customer service experience amongacademic staff in Malaysian public universities. The research model hypothesized that customer involvement and familiarity have significant impact on customer service experience. The study employed a quantitative research. The survey method was utilized and for data collection, a self-administered questionnaire was constructed to gather data from 454 Malaysian public universities’ academic staff. Proportionate stratified random sampling was utilized in this study. Correlation analysisandhierarchical regression analysis were used to analyse the data. All research questions and objectives were answered by performing hierarchical regression analysis. The findings revealed significant relationships between customer involvement and familiarity and customer service experience. Overall,this study provided supportthe importance of highlighting customer involvement and familiarity in managing academic staff’s customer service experience. The results offer several theoretical and practical implications to Malaysian public universities’ administrators, particularly the AAD and also to policy makers and other practitioners especially in designing effective customer service experience strategies